Prognostic Factors in Anti-glomerular Basement Membrane Disease: A Multicenter Study of 119 Patients - Marques, Cindy; Carvelli, Julien; Biard, Lucie; Faguer, Stanislas; Provôt, François; Matignon, Marie; Boffa, Jean-Jacques; Plaisier, Emmanuelle; Hertig, Alexandre; Touzot, Maxime; Moranne, Olivier; Belenfant, Xavier; et al. (Frontiers in Immunology, 2019)
We report the overall and renal outcome in a French nationwide multicenter cohort of 119 patients with anti-glomerular basement membrane (anti-GBM) disease. Sixty-four patients (54%) had an exclusive renal involvement, 7 (6%) an isolated alveolar hemorrhage and 48 (40%) a combined renal and pulmonary involvement. Initial renal replacement therapy (RRT) was required in 78% of patients; 82% received plasmapheresis, 82% cyclophosphamide, and 9% rituximab. ANCA positive (28%) patients were older (70 vs. 47 years, p < 0.0001), less frequently smokers (26 vs. 54%, p = 0.03), and had less pulmonary involvement than ANCA- patients. The 5 years overall survival was 92%. Risk factors of death (n = 11, 9.2%) were age at onset [HR 4.10 per decade (1.89–8.88) p = 0.003], hypertension [HR 19.9 (2.52–157 0.2) p = 0.005], dyslipidemia [HR 11.1 (2.72–45) p = 0.0008], and need for mechanical ventilation [HR 5.20 (1.02–26.4) p = 0.047]. The use of plasmapheresis was associated with better survival [HR 0.29 (0.08–0.98) p = 0.046]. At 3 months, 55 (46%) patients had end-stage renal disease (ESRD) vs. 37 (31%) ESRD-free and 27 (23%) unevaluable with follow-up < 3 months. ESRD patients were older, more frequently female and had a higher serum creatinine level at presentation than those without ESRD. ESRD-free survival was evaluated in patients alive without ESRD at 3 months (n = 37) using a landmark approach. In conclusion, this large French nationwide study identifies prognosis factors of renal and overall survival in anti-GBM patients.